2016
DOI: 10.1016/j.jsc.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Binomial fibers and indispensable binomials

Abstract: Abstract. Let I be an arbitrary ideal generated by binomials. We show that certain equivalence classes of fibers are associated to any minimal binomial generating set of I. We provide a simple and efficient algorithm to compute the indispensable binomials of a binomial ideal from a given generating set of binomials and an algorithm to detect whether a binomial ideal is generated by indispensable binomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Note that in the case of positive lattices the notions of indispensable and weakly indispensable coincide. Recently, a polynomial-time algorithm for computing all indispensable binomials from a given system of binomial generators of an arbitrary binomial ideal was given in [7,Algorithm 1]. Next we complete the classification of indispensable binomials/monomials of lattice ideals in the case of non-positive lattices.…”
Section: 2mentioning
confidence: 99%
“…Note that in the case of positive lattices the notions of indispensable and weakly indispensable coincide. Recently, a polynomial-time algorithm for computing all indispensable binomials from a given system of binomial generators of an arbitrary binomial ideal was given in [7,Algorithm 1]. Next we complete the classification of indispensable binomials/monomials of lattice ideals in the case of non-positive lattices.…”
Section: 2mentioning
confidence: 99%
“…, a t } ⊂ Z n+1 + satisfying a 1 = α + , a t = α − and a i − a i+1 ∈ D for all 1 ≤ i ≤ t. In [9], Diaconis and Sturmfels showed that given a set of generators D of L then I(D) = I L if and only if D is a Markov basis. We cite [5], [6], [7], [9] and [14] for a detailed exposition of Markov bases of lattice ideals and related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Graver bases were originally defined for toric ideals by Sturmfels [Stu96]. Charalambous, Thoma and Vladoiu [CTV16] recently generalised the concept to an arbitrary pure difference ideal I, showing in particular that Gr(I) is finite and includes U(I) as a subset.…”
Section: Introductionmentioning
confidence: 99%